2018
DOI: 10.7150/jca.25351
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Circulating MicroRNAs for Esophageal Squamous Cell Carcinoma: a Systematic Review and Meta-analysis

Abstract: Background and Aim: MicroRNAs, dysregulated in the circulation of esophageal squamous cell carcinoma (ESCC) patient, have been assumed to be with great potential in the diagnosis and prognosis of esophageal cancer. We aimed to review previous articles on ESCC.Methods: A search of electronic databases was performed before Nov 12, 2017. We summarized the identification of microRNA imbalance in the blood of ESCC compared with the healthy controls, with the objective to evaluate the efficiency of microRNAs in diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Therefore, such small molecules have been investigated as serum markers of EC [15][16][17]. A recent meta-analysis, including 35 studies investigating plasma or serum miRNAs of ESCC patients [33], concluded that circulating miRNAs could distinguish ESCC patients from controls with a pooled sensitivity of 79.4% (95% CI, 76.5-82.0%), specificity of 77.9% (95% CI, 74.6-80.8%), and AUC of 0.86 (95% CI, 0.82-0.88). Another meta-analysis exclusively focusing on Asian populations found that miRNAs could distinguish patients with ESCC from controls with 77.7% pooled sensitivity (95% CI, 74.2-80.9%), 80.9% specificity (95% CI, 76.6-84.6%), and AUC of 0.86 (95% CI, 0.83-0.89) [34].…”
Section: Blood Biomarkers Of Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…Therefore, such small molecules have been investigated as serum markers of EC [15][16][17]. A recent meta-analysis, including 35 studies investigating plasma or serum miRNAs of ESCC patients [33], concluded that circulating miRNAs could distinguish ESCC patients from controls with a pooled sensitivity of 79.4% (95% CI, 76.5-82.0%), specificity of 77.9% (95% CI, 74.6-80.8%), and AUC of 0.86 (95% CI, 0.82-0.88). Another meta-analysis exclusively focusing on Asian populations found that miRNAs could distinguish patients with ESCC from controls with 77.7% pooled sensitivity (95% CI, 74.2-80.9%), 80.9% specificity (95% CI, 76.6-84.6%), and AUC of 0.86 (95% CI, 0.83-0.89) [34].…”
Section: Blood Biomarkers Of Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…The reported expression profiles of various circulating miRNAs in ESCC are inconsistent. 18 19 20 21 22 26 In the present study, we selected four miRNAs and investigated their expression levels in the plasma of ESCC patients based on previously published literature. We found that plasma miR-21, miR-31, and miR-375 could be potential biomarkers for ESCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…An I 2 less than 25% represents potentially unimportant heterogeneity; an I 2 of 25% to 50% represents moderate heterogeneity; an I 2 of 50% to 75% represents substantial heterogeneity, and an I 2 of 75% to 100% represents high heterogeneity 10 . A fixed-effect model was used to pool the data if I 2 < 50%, 11 whereas a random-effect model was used if I 2 ≥ 50%. Sensitivity and subgroup analyses were performed to explore the possible sources of heterogeneity if I 2 ≥ 50% 12 .…”
Section: Methodsmentioning
confidence: 99%